1998
DOI: 10.1111/j.1443-1661.1998.tb00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Resection of Rectal Carcinoids Using Double Snare Polypectomy Technique

Abstract: Between 1993 and 1997, 11 patients with rectal carcinoids less than 8 mm in diameter (mean size: 5.5 mm) were endoscopically treated at Tsuboi Hospital. Seven patients were treated by polypectomy or endoscopic mucosal resection. Three of the seven lesions were microscopically diagnosed as having positive submucosal margins. The remaining four showed a distance between the tumor and the resection line(DBTRL) of 0 to 0.33 mm. Then, we attempted endoscopic double snare polypectomy (EDSP) in 1996 and 1997. In four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The heat generated during the resection might have destroyed the neighboring remnant tumor cells,8,31,33,40,41 but we should not exclude the possibility that recurrence or metastasis was not detected in short-term follow-up due to the slow progression of carcinoid tumor 19…”
Section: Discussionmentioning
confidence: 99%
“…The heat generated during the resection might have destroyed the neighboring remnant tumor cells,8,31,33,40,41 but we should not exclude the possibility that recurrence or metastasis was not detected in short-term follow-up due to the slow progression of carcinoid tumor 19…”
Section: Discussionmentioning
confidence: 99%
“…Compared with EMR, ESD is considered a better method for the treatment of rectal carcinoid tumors, but it requires higher technical means and is relatively time consuming and has more complications[ 7 ]. Other improved EMR methods, such as endoscopic double snare polypectomy (EDSP)[ 9 ], EMR with a ligation device (ESMR-L)[ 10 ], EMR with double ligation (ESMR-DL)[ 11 ], or EMR after circumferential pre-cutting (EMR-P)[ 12 ], can remove deeper layers of the tumor without significant complications for small rectal carcinoids. However, the edge remnant is always the problem that needs to be solved for local endoscopic resection.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 Lifting the mucosal layer from the submucosa by injecting saline within the submucosa has made it feasible to remove sessile tumours by endoscopic snare electroexcision. Koyama et al 4 reported the usefulness of double snare polypectomy for the successful resection of small rectal carcinoid tumours.…”
Section: Endoscopic Resection Of Carcinoid Tumoursmentioning
confidence: 99%
“…The application of endoscopic resection has not been a common treatment because these tumours are sessile and are generated from the deep mucosal layer towards the submucosa; polypectomy or mucosal resection by conventional methods has not proved useful for removing whole tumours. 4 We have found that by lifting the mucosa away from the submucosa with an injection of physiological saline into the submucosa, followed by aspirating the lesion into a short transparent overcap, a sessile tumour can easily be resected using an endoscopic approach.…”
Section: Introductionmentioning
confidence: 99%